TEACHING THROUGH PHILOSOPHY AND THE WILL TO POWER: FOR A LIBERATING TEACHING - Monteiro Gimenez de Oliveira, Rodrigo (Revista Gênero e Interdisciplinaridade, 2023)
This work permeates the Nietzschean concept about the Will to Power on the educational system today, aiming at a more active and effective Teaching of Philosophy. Where the philosophical thought of Friedrich Nietzsche and other philosophers end up approaching excerpts from history in the construction of the teaching of philosophy. Showing that there may be the possibility of a liberating teaching of philosophy, which turns out to be a driving force beyond banking education and which is a plausible possibility. We will also make a comparison about the thought of Friedrich Nietzsche and Lilian Bacich. The bibliographic review carried out in this work was based on the concept of Will Power linked to liberating teaching, aiming to overcome certain barriers applied to contemporary teaching, allowing the student to reach the autonomy of his own knowledge with criticality, thus being the author of his own will.